Clinical profile and outcome of HIV-TB Co‑Infection at a centre of excellence for HIV care - Narasimhamurthy, Diwakar Tumkur; Thomas, David Mathew; Krishnegowda, Ravi; Thayyil, Asif Ali; Mallesh, Shruthi K R Nagar; Fahad, Abdul; Chikkahonappa, Raghavendra Byadigere (Asian Journal of Medical Sciences, 2018)
Background: Tuberculosis (TB) and Human Imuunodeficiency Virus (HIV) co-infection has detrimental effects on both the individual and the health care system especially in resource limited countries like India. Tuberculosis ranks among the most common cause of death in HIV patients. In this review we have analysed the clinical and immunological characteristics of HIV-TB coinfected patients and their clinical outcomes. Aims and Objectives: To assess the co-relation between socio-demographic characteristics, clinical and immunological Profile of HIV-TB co-infected patients and the clinical outcome. Materials and Methods: A retrospective clinical study of patient records at the Centre of Excellence for anti-retroviral therapy was done. The records of HIV-TB co-infected patients were collected and data extracted pertaining to the socio- demographic characteristics, clinical profiles and outcomes. Results: Among the 377 cases included as per criteria, 76.9 % completed the treatment for TB while 23.1% patients died before treatment completion. Twenty-nine point seven percent of the patient population constituted women, while 0.5% was transgenders. Regarding the pattern of tuberculosis, 58.4% patients had extra pulmonary TB while 39.5% and 2.1% of the study population were diagnosed as pulmonary and disseminated TB respectively. Mean baseline CD4 count was 191 cells/mm3 and the mean CD4 count during first and second follow up were 298 and 362 cells/mm3 respectively. There was a statistically significant correlation noted with poor clinical outcomes and low baseline CD4 counts. Conclusion: Age, gender, the clinical pattern of tuberculosis and the treatment category did not have a statistically significant association on the outcome. We found that the TB associated mortality in HIV co-infected patients had a direct correlation with the stage of HIV at presentation as there was a strongly significant association between low CD4 counts and adverse clinical outcomes. Asian Journal of Medical Sciences Vol.9(2) 2018 19-24